Associations of modifiable behavioral risk factor combinations at 65-74 years old with cognitive healthspan over 20 years. - Smagula, Stephen F; Biggs, Mary L; Jacob, Mini E; Rawlings, Andreea M; Odden, Michelle C; Arnold, Alice; Newman, Anne B; Buysse, Daniel J (Psychosom Med, 2022)
OBJECTIVE: Behavioral risk factors for dementia tend to co-occur and inter-relate, especially poor diet, physical inactivity, sleep disturbances, and depression. Having multiple of these modifiable behavioral risk factors (MBRFs) may predict a particularly shortened cognitive healthspan, and therefore, may signal high-risk status/high intervention need. METHODS: This secondary analyses of data from the Cardiovascular Health Study included 3149 participants aged 65-74 years (mean age = 69.5, standard deviation (SD) = 2.5; 59.6% female). MBRF exposures were self-reports regarding: (1) diet, (2) activity, (3) sleep, and (4) depression symptoms. We primarily analyzed MBRF counts. Over up to 26 years of follow-up, we assessed the: (1) number of remaining cognitively healthy life years (CHLYs); and (2) percentage of remaining life years (LYs) that were CHLYs (%CHLY). We estimated CHLYs as time before a dementia diagnosis, cognitive screener scores indicating impairment, proxy port indicating significant cognitive decline, or dementia medication use. RESULTS: Participants averaged a remaining 16 LYs (SD = 7), 12.2 CHLYs (SD = 6.6), and 78.1% of LYs being CHLYs (SD = 25.6). Compared with having no MBRFs, having one was associated with ~1 less LY and CHLY, but not a relatively lower %CHLY. In contrast, having 3+ MBRFs was associated with about 2-3 fewer LYs and CHLYs as well as about 6% lower %CHLY (95% confidence interval: -9.0, -2.5 %CHLYs), p = 0.001). CONCLUSIONS: MBRF-related reductions in the cognitive healthspan are most apparent when people have multiple MBRFs. Future research is needed to determine if/how behavioral risks converge mechanistically, and if dementia prevention efficacy improves when targeting MBRF combinations.